2016
DOI: 10.1080/13880209.2016.1211714
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous screening and analysis of antiplatelet aggregation active alkaloids from Rhizoma Corydalis

Abstract: Objective: The antiplatelet aggregation compounds in Rhizoma Corydalis were screened to validate its traditional medicinal use. Material and methods: Total alkaloid extract (TAE) of Rhizoma Corydalis was obtained by refluxing 100 g Rhizoma Corydalis powder with 600 mL 70% ethanol, and purified by acidification (20% HCl) and alkalization (5 M NaOH) process. Potential antiplatelet aggregation compounds in TAE were screened by a method involving platelet bio-specific extraction and HPLC-DAD/LC-MS analysis. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…We further identified myogenic alkaloids including stylopine, corydaline, canadine and coptisine, and canadine showed the strongest myogenic activity among the tested compounds ( Figure 2 ). Canadine has been found in herbal plants [ 32 , 33 ] showing relaxant [ 34 ], anti-oxidative [ 35 ], anti-platelet aggregation [ 36 ], anti-Alzheimer’s disease [ 37 ], anti-fibrotic and wound-healing activities [ 38 ]. In this study, we first observed the myogenesis-stimulating activity of canadine.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified myogenic alkaloids including stylopine, corydaline, canadine and coptisine, and canadine showed the strongest myogenic activity among the tested compounds ( Figure 2 ). Canadine has been found in herbal plants [ 32 , 33 ] showing relaxant [ 34 ], anti-oxidative [ 35 ], anti-platelet aggregation [ 36 ], anti-Alzheimer’s disease [ 37 ], anti-fibrotic and wound-healing activities [ 38 ]. In this study, we first observed the myogenesis-stimulating activity of canadine.…”
Section: Discussionmentioning
confidence: 99%
“…A total of more than 20 alkaloids have been identified from the tubers of CYHS, including corydaline, dl-tetrahydropalmatine, protopine, L-tetraline, L-tetrahydrocoptisine (L-stylopin), dl-tetrahydroberberine, L-tetrahydrocolumbamine, corybulbine, β-herbadol, β-homoche-lidonine, coptisine, dehydrocorydaline, and corydalmine. [82][83][84][85] CYHS is currently used clinically, mainly for the treatment of drug addiction, 86 as well as for its antiaging, anxiolytic, 87 and antiplatelet aggregation 88 properties and for the treatment of depression. 89 Qi stagnation and blood stasis are primary causes of depression in the theory of TCM.…”
Section: Polygala Tenuifolia Willdmentioning
confidence: 99%
“…CYHS is currently used clinically, mainly for the treatment of drug addiction, 86 as well as for its antiaging, anxiolytic, 87 and antiplatelet aggregation 88 properties and for the treatment of depression. 89 Qi stagnation and blood stasis are primary causes of depression in the theory of TCM.…”
Section: Pharmacological Studies Of the Active Compounds Of Nine Chinmentioning
confidence: 99%
“…These have a wide range of pharmacological activities such as: Antioxidant, antibacterial, antiviral, anticancer, analgesic, and promotion of blood circulation. For analysis of alkaloids in extracts obtained from Corydalis species, C18 column and mobile phases consisted of acetonitrile, water and formic acid [19,20,21,22], ammonium acetate [23], formic acid and ammonium acetate [24], acetate buffer at pH 5.0 [20], ammonium hydroxide [25], acetonitrile, water, acetic acid, and diethylamine [26], or acetic acid with triethylamine [27] rarely methanol, water with the addition of formic acid [28] or formic acid and ammonium acetate [29] were applied. The inhibitory effects on human tumor cell lines: A549, SK-OV-3, SK-MEL-2, and HCT-15 of tubers of Corydalis ternata were found [30].…”
Section: Introductionmentioning
confidence: 99%